2015
DOI: 10.1080/15384047.2015.1026479
|View full text |Cite
|
Sign up to set email alerts
|

Tumor profiling of gastric and esophageal carcinoma reveal different treatment options

Abstract: Background: NCCN states that chemotherapies for advanced esophageal and gastric cancers may be used interchangeably. Biomarkers from gastroesophageal cancer patients were interrogated to identify actionable alterations with therapeutic implications. Methods: 666 gastric and 640 esophageal cancer cases referred to Caris Life Sciences between 2009 thru 2013 were evaluated. Specific testing was performed, which included a combination of sequencing (Sanger, NGS) and protein expression (IHC). Results: In the comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 22 publications
(17 reference statements)
3
15
0
Order By: Relevance
“…Moreover, overexpression of SPARC was correlated with a poor prognosis of patients with EAC [36]. Another study showed a significant difference in the SPARC levels in tumor tissue between gastric cancer and ESCC (15% vs. 34%) [37], suggesting SPARC as a potential novel therapeutic target. High expression levels of BGN have also been detected in a variety of human epithelial cancers [38,39], indicating a potentially important role in tumor development.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, overexpression of SPARC was correlated with a poor prognosis of patients with EAC [36]. Another study showed a significant difference in the SPARC levels in tumor tissue between gastric cancer and ESCC (15% vs. 34%) [37], suggesting SPARC as a potential novel therapeutic target. High expression levels of BGN have also been detected in a variety of human epithelial cancers [38,39], indicating a potentially important role in tumor development.…”
Section: Discussionmentioning
confidence: 97%
“…Conflicting clinical trial reports exist regarding the role of ERCC1 expression in predicting cisplatin treatment on gastric cancer: some claimed that patients benefit more from low ERCC1 expression (De Dosso et al, 2013;Hirakawa et al, 2013;Kwon et al, 2007;Metzger et al, 1998;Miura et al, 2015), some stated the opposite (Baek et al, 2006;Bamias et al, 2010;Kim et al, 2011), while still others found no connection at all (Sonnenblick et al, 2012).…”
Section: Mcts Can Explain Paradoxical Clinical Trial Resultsmentioning
confidence: 99%
“…Additionally, Miura et al indicated that negative expression of the MGMT gene was observed in 45% of the gastroesophageal tumors on the basis of biomarker profiling, suggesting potential sensitivity to temozolomide. 46 Therefore, it is necessary to detect the MGMT promoter methylation status in patients with gastric cancer to develop individualized treatment programs when they are treated with temozolomide.…”
Section: Discussionmentioning
confidence: 99%